Spontaneous mechanical and electrical activities of human calf musculature at rest assessed by repetitive single‐shot diffusion‐weighted MRI and simultaneous surface electromyography. Issue 5 (17th September 2017) - Schwartz, Martin; Steidle, Günter; Martirosian, Petros; Ramos‐Murguialday, Ander; Preißl, Hubert; Stemmer, Alto; Yang, Bin; Schick, Fritz
Abstract : Purpose: Assessment of temporal and spatial relations between spontaneous mechanical activities in musculature (SMAM) at rest as revealed by diffusion‐weighted imaging (DWI) and electrical muscular activities in surface EMG (sEMG). Potential influences of static and radiofrequency magnetic fields on muscular activity on sEMG measurements at rest were examined systematically. Methods: Series of diffusion‐weighted stimulated echo planar imaging were recorded with concurrent sEMG measurements. Electrical activities in sEMG were analyzed by non‐parametric Friedman and two‐sample Kolmogorov–Smirnov test. Direct correlation of both modalities was investigated by temporal mapping of electrical activity in sEMG to DWI repetition interval. Results: Electrical activities in sEMG and number of visible SMAMs in DWI showed a strong correlation (ρ = 0.9718). High accordance between sEMG activities and visible SMAMs in DWI in a near‐surface region around sEMG electrodes was achieved. Characteristics of sEMG activities were almost similar under varying magnetic field conditions. Conclusion: Visible SMAMs in DWI have shown a close and direct relation to concurrent signals recorded by sEMG. MR‐related magnetic fields had no significant effects on findings in sEMG. Hence, appearance of SMAMs in DWI should not be considered as imaging artifact or as effects originating from the special conditions of MR examinations. Spatial and temporal distributions of SMAMs indicate characteristics of spontaneous (microscopic) mechanical muscular action at rest. Therefore, DWI techniques should be considered as non‐invasive tools for studying physiology and pathophysiology of spontaneous activities in resting muscle. Magn Reson Med 79:2784–2794, 2018. © 2017 International Society for Magnetic Resonance in Medicine.